Abundance and Diversity of Dockerin-Containing Proteins in the Fiber-Degrading Rumen Bacterium, Ruminococcus flavefaciens FD-1 - Rincon, Marco T. (Public Library of Science, 2010)
BACKGROUND: The cellulosome is a multi-enzyme machine, which plays a key role in the breakdown of plant cell walls in many anaerobic cellulose-degrading microorganisms. Ruminococcus flavefaciens FD-1, a major fiber-degrading bacterium present in the gut of herbivores, has the most intricate cellulosomal organization thus far described. Cellulosome complexes are assembled through high-affinity cohesin-dockerin interactions. More than two-hundred dockerin-containing proteins have been identified in the R. flavefaciens genome, yet the reason for the expansion of these crucial cellulosomal components is yet unknown. METHODOLOGY/PRINCIPAL FINDINGS: We have explored the full spectrum of 222 dockerin-containing proteins potentially involved in the assembly of cellulosome-like complexes of R. flavefaciens. Bioinformatic analysis of the various dockerin modules showed distinctive conservation patterns within their two Ca(2+)-binding repeats and their flanking regions. Thus, we established the conceptual framework for six major groups of dockerin types, according to their unique sequence features. Within this framework, the modular architecture of the parent proteins, some of which are multi-functional proteins, was evaluated together with their gene expression levels. Specific dockerin types were found to be associated with selected groups of functional components, such as carbohydrate-binding modules, numerous peptidases, and/or carbohydrate-active enzymes. In addition, members of other dockerin groups were linked to structural proteins, e.g., cohesin-containing proteins, belonging to the scaffoldins. CONCLUSIONS/SIGNIFICANCE: This report profiles the abundance and sequence diversity of the R. flavefaciens FD-1 dockerins, and provides the molecular basis for future understanding of the potential for a wide array of cohesin-dockerin specificities. Conserved differences between dockerins may be reflected in their stability, function or expression within the context of the parent protein, in response to their role in the rumen environment.